2008
DOI: 10.1111/j.1365-2036.2008.03794.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial: oral feeding with a soft diet compared with clear liquid diet as initial meal in mild acute pancreatitis

Abstract: SUMMARY BackgroundIn mild acute pancreatitis, traditional treatment has been initial fasting and oral refeeding with clear liquids to prevent adverse gastrointestinal events such as pain. The diet is gradually progressed to soft solids and hospital discharge is planned based on patients' tolerance to a solid diet.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(75 citation statements)
references
References 11 publications
2
59
0
11
Order By: Relevance
“…Thirty-three articles (21 articles containing patients suffering from SAP as well as 12 articles with MAP patients) were selected. They contained two nonrandomized and 31 randomized controlled clinical trials (Table 2) [16][17][18][19][20][21][22][23][24][25][26][27]29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Finally, statistical analyses were performed on data from articles where both EN and NPO groups were presented, the trial was randomized, and the relevant data were available.…”
Section: Inclusions and Exclusionsmentioning
confidence: 99%
“…Thirty-three articles (21 articles containing patients suffering from SAP as well as 12 articles with MAP patients) were selected. They contained two nonrandomized and 31 randomized controlled clinical trials (Table 2) [16][17][18][19][20][21][22][23][24][25][26][27]29,[31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Finally, statistical analyses were performed on data from articles where both EN and NPO groups were presented, the trial was randomized, and the relevant data were available.…”
Section: Inclusions and Exclusionsmentioning
confidence: 99%
“…The results support the hypothesis that alcohol played a crucial role in pancreatitis mortality in Russia over the past decades. This study also indicates that substantial proportion of pancreatitis deaths in Russia is due to acute effect of binge drinking 9 . Results of one study had 964 admissions with the diagnosis acute pancreatitis, making an incidence of 5.64 per 100 000 inhabitants per year.…”
Section: Literature Surveymentioning
confidence: 82%
“…A recent study has shown that initiating re-feeding with low fat soft diet is safe and can reduce hospitalization, when compared with clear liquid diet. 24 In biliary pancreatitis, a sphincterotomy can relieve the obstruction. In cases of mild gallstone pancreatitis, one small study of 50 patients found early gallbladder removal was safe and associated with shorter hospital stay.…”
Section: Discussionmentioning
confidence: 99%